The Influence Of Employee Motivation And Organizational Commitment On Employee Performance With Organizational Culture Organization As An Intervening Variable In BPJS Employment Branch Office Range - Muslim, Aziz; Indrawan, Muhammad Isa (International Publisher, 2024)
In this study, researchers wanted to see the direct and indirect effects between employee motivation variables and organizational commitment as independent variables and organizational culture as an intervening variable and employee performance as the dependent variable. This type of research uses quantitative, this research was conducted at the BPJS Employment Branch Office in Kisaran. The population of this study was 60 employees and the sample used was all the population using the saturated sample technique. The data source used is primary data sources and the data collection carried out is to spread the questionnaire. The research model used is phat analysis with smart PLS version 3.3.3. as a research measurement tool. The results of this study are as follows: Employee motivation has a positive and significant effect on employee performance with an original sample value of 0.652 and P values of 0.000. Employee motivation has a positive and significant effect on organizational culture with an original sample value of 0.642 and p values of 0.000. Organizational commitment has a positive and insignificant effect on employee performance with an original sample value of 0.090 and p values of 0.229. Organizational commitment has a positive and insignificant effect on organizational culture with an original sample value of 0.109 and p values of 0.256. Organizational culture has a positive and significant effect on employee performance with an original sample value of 0.206 and p values of 0.003. Employee motivation has a positive and insignificant effect on employee performance through organizational culture indirectly with the original sample result of 0.132 and p values 0.250. Organizational commitment has a positive and significant effect on employee performance through organizational culture with an original sample value of 0.022 and p values of 0.011.